2018
DOI: 10.3758/s13423-018-1518-6
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling cross-language orthographic neighborhood from markedness effects in L2 visual word recognition

Abstract: Previous research has reported that lexical access in bilinguals is language non-selective. In the present study, we explored the extent to which cross-language orthographic neighborhood size (N-size) effects, an index of language non-selectivity, should be dissociated from markedness effects, a sub-lexical orthographic variable referring to the degree of language- shared (unmarked) versus specific (marked) orthography. Two proficiency groups of French/English bilinguals performed an English (L2) lexical decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The bilingual literature parallels the monolingual literature; it has reported mixed patterns of facilitatory, inhibitory, and null within-language and cross-language orthographic neighborhood density effects among healthy bilingual young adults (aged 18-30) across their L1 and L2 (e.g., Beauvillain, 1992;de Groot et al, 2002;Dirix et al, 2017, Commissaire et al, 2019Grainger and Dijkstra, 1992;Van Heuven et al, 1998;Lemhöfer et al, 2008;Midgley et al, 2008;Grossi et al, 2012;Meade et al, 2018;Mulder et al, 2018). As discussed previously, these between-study differences are likely driven by methodologyrelated factors, including whether orthographic neighborhood frequency was accounted for, as well as by participant-related factors.…”
Section: Findings From Response-based Literaturementioning
confidence: 92%
“…The bilingual literature parallels the monolingual literature; it has reported mixed patterns of facilitatory, inhibitory, and null within-language and cross-language orthographic neighborhood density effects among healthy bilingual young adults (aged 18-30) across their L1 and L2 (e.g., Beauvillain, 1992;de Groot et al, 2002;Dirix et al, 2017, Commissaire et al, 2019Grainger and Dijkstra, 1992;Van Heuven et al, 1998;Lemhöfer et al, 2008;Midgley et al, 2008;Grossi et al, 2012;Meade et al, 2018;Mulder et al, 2018). As discussed previously, these between-study differences are likely driven by methodologyrelated factors, including whether orthographic neighborhood frequency was accounted for, as well as by participant-related factors.…”
Section: Findings From Response-based Literaturementioning
confidence: 92%
“…Marked words are words with rather language‐specific (L1 or L2) sub‐lexical orthographic patterns (e.g., ‐ght and ‐oeu are specific to English and French, respectively), whereas unmarked words contain shared orthographic patterns across languages (e.g., ‐ain is common in both English and French). Bilingual research among adults has reported faster processing of L2 marked words compared with unmarked words in tasks that require judging the language membership of the word (i.e., language decision task, Casaponsa, Carreiras, & Duñabeitia, 2014; Vaid & Frenck‐Mestre, 2002) or deciding whether the item is a real L2 word or not (i.e., lexical decision task, Commissaire, Audusseau, & Casalis, 2019). Despite a lack of empirical studies on how L2 marked versus unmarked words are read by young L2 learners, either typical or dyslexic readers, marked words seem to be less easily learned compared with unmarked words when using a word‐learning paradigm (with an artificial language, Bartolotti & Marian, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these two studies focusing on neighbourhood size effects across languages strongly challenge the existence of cross-language lexical competition in pure monolingual tasks such as lexical decision, with null effects being obtained, perhaps due to confounds with orthographic markedness in previous studies (Commissaire et al, 2019;Mulder et al, 2018). It should also be noted that the few eye-tracking studies on the topic also reported puzzling results, as cross-language facilitatory neighbourhood size effects were found in more natural sentence reading experiments (Dirix et al, Experiment 2;Whitford & Titone, 2019), which also does not support the lexical competition hypothesis.…”
mentioning
confidence: 99%
“…This hypothesis is supported by evidence of lexical competition effects between cross-language orthographic neighbour words such as fire — rire (laugh) in the English/French language pair (Bijeljac-Babic et al, 1997; Dijkstra et al, 2010; Dirix et al, 2017; Experiment 1; Grossi et al, 2012; Midgley et al, 2008; Van Heuven et al, 1998), a mechanism that is therefore implemented in several models such as the Bilingual Interactive Activation model (BIA, Van Heuven et al, 1998), and its extension BIA+ (Dijkstra & Van Heuven, 2002). However, the growing interest on sub-lexical orthographic coding, and especially on the orthographic markedness effect, raises new issues about language detection mechanisms (Casaponsa et al, 2014, 2015, 2020; Casaponsa & Duñabeitia, 2016; Commissaire et al, 2014, 2019; Hoversten et al, 2017; Oganian et al, 2016; Vaid & Frenck-Mestre, 2002; Van Kesteren et al, 2012) and also suggests that this variable could modulate the degree of language non-selectivity in bilingual lexical access (Casaponsa & Duñabeitia, 2016). This study aimed to investigate masked L2-to-L1 orthographic priming, an index of cross-language lexical competition, in French/English bilinguals while considering words’ orthographic sub-lexical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation